Reading error mechanisms of levinson dyslexia theory: a perspective in Malaysia - Subramaniam, Vijayaletchumy; Kunasegran, Kavenia (Human Resource Management Academic Research Society, 2022)
It is known that children diagnosed with dyslexia have difficulties in language learning, especially where reading and writing is concerned. Dyslexics find it difficult to discriminate letters visually and auditorily. This study is done to examine the reading errors in Malay language among dyslexic students. The study sample comprises of 10 dyslexic students chosen from Ampang dyslexia centre of Malaysia Dyslexia Association. This study leans on the Levinson Theory (1993) that focuses on seven types of reading error mechanisms, namely removal, transfer, insertion, replacement, reversal, condensation, addition or wild guesses. The study data was compiled through observations and testing. Researcher used reading texts in Malay language according to the suitability of the learning level as the study tool in examining the reading errors of dyslexic students. The study outcome proves that dyslexic students have shown some difficulties in several reading aspects, which are removal, reversal, replacement, insertion and wild guesses. All these five types of reading errors have been found to support the Dyslexic Levison Theory (1993) and the outcome also shows several reading errors done by the dyslexic students are beyond the expectation and findings of the theory. Derived from this study, further researches can be focused on the interventions and learning techniques that are suitable to the level of learning of dyslexic students.